2018
DOI: 10.4266/acc.2016.00689
|View full text |Cite
|
Sign up to set email alerts
|

Negative Pressure Pulmonary Hemorrhage after Laryngospasm during the Postoperative Period

Abstract: Negative pressure pulmonary hemorrhage (NPPH) is an uncommon complication of upper airway obstruction. Severe negative intrathoracic pressure after upper airway obstruction can increase pulmonary capillary mural pressure, which results in mechanical stress on the pulmonary capillaries, causing NPPH. We report a case of acute NPPH caused by laryngospasm in a 25-year-old man during the postoperative period. Causative factors of NPPH include negative pulmonary pressure, allergic rhinitis, smoking, inhaled anesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…There have been several reports of NPPH in the perioperative period, triggered by laryngospasm after extubation 3) . In Japan, only a few other cases of choking due to food aspiration and sleep apnea have been reported 6,7) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reports of NPPH in the perioperative period, triggered by laryngospasm after extubation 3) . In Japan, only a few other cases of choking due to food aspiration and sleep apnea have been reported 6,7) .…”
Section: Discussionmentioning
confidence: 99%
“…However, negative pressure pulmonary hemorrhage (NPPH), which is caused by excessive negative pressure in the thoracic cavity, is another differential disease for acute respiratory exacerbation. NPPH is caused by upper airway obstruction, particularly triggered by laryngospasm after extubation in the perioperative period 3) . However, there have been no reports of NPPH caused by laryngospasm without an obvious invasive factor.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that a more detailed examination is needed to determine whether this mild mitral regurgitation was the cause of unilateral DAH in this case, but such an examination was not performed in this patient. In 2016, Han et al [ 10 ] reported negative pressure pulmonary hemorrhage that occurred after laryngospasm in the postoperative period. In 2016, Choe et al [ 11 ] reported DAH after transfemoral cerebral angiography in patients taking clopidogrel, and there is a potential for DAH associated with neuro-intervention in patients with hemoptysis and respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…A typical perioperative condition is laryngospasm, which occurs after extubation of an endotracheal tube. [ 9 , 10 ] Other conditions may include biting of the endotracheal tube or the laryngeal mask. [ 11 , 12 ] Although most patients experience negative pressure pulmonary edema, hemorrhages can develop in the alveoli, and the destruction of pulmonary capillaries plays an important role in overt pulmonary hemorrhage.…”
Section: Discussionmentioning
confidence: 99%